Toxoplasma gondii-Derived Synthetic Peptides Containing B- and T-Cell Epitopes from GRA2 Protein Are Able to Enhance Mice Survival in a Model of Experimental Toxoplasmosis - Bastos, Luciana M.; Macêdo, Arlindo G.; Silva, Murilo V.; Santiago, Fernanda M.; Ramos, Eliezer L. P.; Santos, Fabiana A. A.; Pirovani, Carlos P.; Goulart, Luiz R.; Mineo, Tiago W. P.; Mineo, José R. (Frontiers in Cellular and Infection Microbiology, 2016)
Toxoplasmosis is a zoonosis distributed all over the world, which the etiologic agent is an intracellular protozoan parasite, Toxoplasma gondii. This disease may cause abortions and severe diseases in many warm-blood hosts, including humans, particularly the immunocompromised patients. The parasite specialized secretory organelles, as micronemes, rhoptries and dense granules, are critical for the successful parasitism. The dense granule protein 2 (GRA2) is a parasite immunogenic protein secreted during infections and previous studies have been shown that this parasite component is crucial for the formation of intravacuolar membranous nanotubular network (MNN), as well as for secretion into the vacuole and spatial organization of the parasites within the vacuole. In the present study, we produced a monoclonal antibody to GRA2 (C3C5 mAb, isotype IgG2b), mapped the immunodominant epitope of the protein by phage display and built GRA2 synthetic epitopes to evaluate their ability to protect mice in a model of experimental infection. Our results showed that synthetic peptides for B- and T-cell epitopes are able to improve survival of immunized animals. In contrast with non-immunized animals, the immunized mice with both B- and T-cell epitopes had a better balance of cytokines and demonstrated higher levels of IL-10, IL-4 and IL-17 production, though similar levels of TNF-alpha and IL-6 were observed. The immunization with both B- and T-cell epitopes resulted in survival rate higher than 85% of the challenged mice. Overall, these results demonstrate that immunization with synthetic epitopes for both B- and T-cells from GRA2 protein can be more effective to protect against infection by T. gondii.